Pengelolaan sampah dan pembuatan pupuk organik di Lingkungan II Kelurahan Pinaesaan Kecamatan Wenang Kota Manado Provinsi Sulawesi Utara - Silooy, Fanny; Pangkey, Henneke (Universitas Sam Ratulangi, 2021)
The purpose of waste management and composting activity in Lingkungan II, Pinaesaan Sub-District, Wenang District, Manado City was to develop transformation that increases level of knowledge, skill, ability, attitude and motivation according to planned activities, whereas the method used is in the form of counselling. On this activity, the result was obtained where the group of housewives gave positive responses and learned how to make compost from household waste